Restoration ecophysiology: an ecophysiological approach to improve restoration strategies and outcomes in severely disturbed landscapes - Valliere, Justin M.; Ruscalleda Alvarez, Jaume; Cross, Adam; Lewandrowski, W.; Riviera, Fiamma; Stevens, Jason C.; Tomlinson, Sean; Tudor, Emily P.; Wong, Wei San; Yong, Jean W.H.; Veneklaas, E.J. (WILEY, 2022)
As human activities destroy and degrade the world's ecosystems at unprecedented scales, there is a growing need for evidence-based methods for ecological restoration if we are to preserve biodiversity and ecosystem services. Mining represents one of the most severe anthropogenic disturbances, often necessitating intensive intervention to restore the most basic attributes of native ecosystems. Despite examples of successful mine-site restoration, re-establishing native vegetation in these degraded landscapes remains a significant challenge. Plant ecophysiology—the study of the interactions between plants and the environment—can provide a useful framework for evaluating and guiding mine-site restoration. By understanding the physiological mechanisms that allow plants to establish and persist in these highly disturbed environments, practitioners may be able to improve restoration outcomes. Specifically, methods in plant ecophysiology can inform site preparation and the selection of plant material for restoration projects, aid in monitoring restoration progress by providing additional insight into plant performance, and ultimately improve our ability to predict restoration trajectories. Here, we review the challenges and benefits of integrating an ecophysiological perspective to mine-site restoration in Western Australia, a global hotspot of biodiversity and mining operations. Using case studies and examples from the region's diverse ecosystems, we illustrate how an ecophysiological approach can guide the restoration of some of the world's most severely disturbed landscapes. With careful selection of study species and traits and consideration of the specific environmental conditions and stressors within a site, the restoration ecophysiology framework outlined here has the potential to inform restoration strategies across ecosystems.